The Influence of Service Quality, Institutional Reputation, Students Satisfaction on Students Loyalty in Higher Education Institution - Bakrie, Muhammad; Sujanto, Bedjo; Rugaiyah, Rugaiyah (International Journal for Educational and Vocational Studies, 2019)
Research highlights the influence of service quality, institutional reputation, student satisfaction in building student loyalty. Quantitative approach was used with a survey method. The research respondents were 185 students from PGRI University Palembang. Analysis techniques using variance-based structural equation models (SEM) SmartPLS. The results of the study shows that service quality has a significant effect on reputation and student satisfaction, but service quality and student satisfaction have no significant effect on student loyalty. On the contrary, the reputation of an institution has a very significant direct effect on loyalty. Student service quality has a significant indirect effect on student loyalty through the reputation of the institution, this implies that the reputation of the institution carries a relative influence relationship between service quality on student loyalty. These findings can help higher education institutions to make better strategic plans to increase student loyalty.